2015
DOI: 10.1002/chem.201502114
|View full text |Cite
|
Sign up to set email alerts
|

How and Why Does Ni0 Promote Smooth Etheric CO Bond Cleavage and CC Bond Formation? A Theoretical Study

Abstract: Ni-catalyzed cross-coupling between aryl alkyl ethers (ArOR) and Grignard reagents (RMgBr), known since 1979, proceeds under mild conditions in many cases. Although the reaction routes of various synthetic protocols involving transition-metal-catalyzed C-O bond activation have been elucidated, the mechanism of this etheric Kumada-Tamao-Curriu reaction remains enigmatic. This is because oxidative addition of inert etheric C-O to Ni(0) is thermodynamically and kinetically unfavorable, making it hard to explain t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
84
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 76 publications
2
84
1
1
Order By: Relevance
“…46) Computational studies by Nakamura and colleagues, 55) Liu and colleagues, 56) Martin and colleagues, 46) and us 14) clearly demonstrated that OA of a E C-O bond generally involves a very high activation barrier (Chart 2(1)), even considering the Lewis acidity of Mg (Chart 2(2)). This could be attributed to the high stability of the E C-O bond and the weak interaction between the E C-O moiety and Ni(0) species.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…46) Computational studies by Nakamura and colleagues, 55) Liu and colleagues, 56) Martin and colleagues, 46) and us 14) clearly demonstrated that OA of a E C-O bond generally involves a very high activation barrier (Chart 2(1)), even considering the Lewis acidity of Mg (Chart 2(2)). This could be attributed to the high stability of the E C-O bond and the weak interaction between the E C-O moiety and Ni(0) species.…”
Section: Resultsmentioning
confidence: 93%
“…Considering the nucleophilicity of Ni (0) Cornella and Martin, 19) and our group 14) have suggested that, instead of the neutral Ni(0) or anionic ] − species, the [C-Ni(0)]-ate species [57][58][59][60] is involved. In 2015, we reported the first systematic mechanistic study on the Ni-catalyzed…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations